Intertextual parallels in the poetry of Bakhyt Kairbekov - Abdrakhmanova, Э.А.; Takhan, С.Ш. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The article attempts to explore intertextual parallels between the poetry of Bakhyt Kairbekov and the Japanese poets Basho and Takuboku. The conducted intertextual analysis made it possible to identify the presence of intertextual connections, to determine the similarity of themes, motives and images. Intertextual references enrich the meaning of lyrical works and provide a deeper understanding of the intentions and thoughts of the writers. The artistic context of poetic works by authors of different cultures and eras intersects, giving breadth and globality to the sociocultural issues and philosophical thought raised. The semiotic structure of the poetics of B. Kairbekov and Japanese authors acts as a special mechanism for transmitting information about the surrounding world, traditional culture, customs, the interweaving of national symbols, language and thinking. At the same time, the existing intertextual connections and parallels between the poetic works of Kairbekov, Basho and Takuboku do not at all cancel the well-deserved right of each of the poets to their own individual style, the uniqueness of poetic handwriting.Through this analysis, we hope to gain a deeper understanding of how poetry can transcend cultural and linguistic boundaries, interpret national and universal problems in the context of intercultural communication.